Stingray-ADR technique creating a channel between double CTO lesions in a previous CABG patient - Huan Wang; You-hu Chen; Gen-rui Chen; Cheng-xiang Li; Hao-kao Gao (BMC Cardiovascular Disorders)
Abstract Patients presenting with previous coronary artery bypass grafting (CABG) exhibit an accelerated progression of atherosclerosis in native coronary arteries following surgical revascularization. When saphenous vein grafts (SVGs) become diseased or occluded, the treatment of the entire native vessels becomes significantly more challenging. Herein, we present a patient who was admitted to our hospital due to heart failure. He had undergone CABG 12 years earlier, with a left internal mammary artery (LIMA) grafted to the left anterior descending (LAD) artery, a saphenous vein graft (SVG) to the first diagonal branch (D1), and another SVG to the right coronary artery (RCA). Furthermore, a stent was implanted in the SVG to the RCA five years ago. During the current admission, angiography identified multiple chronic total occlusion (CTO) lesions in the native proximal LAD and RCA, as well as in the SVG-D1, along with in-stent occlusion of the SVG to RCA. The percutaneous coronary intervention (PCI) strategy primarily focused on recanalization of the CTO in the RCA. We successfully implemented the Stingray-based antegrade dissection reentry (ADR) technique in the LAD CTO lesion to establish a critical channel. Leveraging this channel, we subsequently accomplished retrograde recanalization of the RCA CTO via septal collateral vessels. This case demonstrates that the Stingray-ADR technique can serve as a promising and effective approach in facilitating the recanalization of more complex multi-vessel CTO lesions. Clinical trial number: Not applicable.